Job Satisfaction and Employee Engagement of Generation X, Y, and Z in the Industrial Timber Plantation Sector of Kalimantan: The Role of Work Environment, Organizational Culture, and Digital Literacy - Maurits Sahata Sipayung; Tina Tri Wulansari (Jurnal Ragam Pengabdian, 2026)
This study explores the effects of Work Environment, Organizational Culture, and Digital Literacy on Job Satisfaction and Employee Engagement, with Generational Cohort (X, Y, and Z) as a moderating variable. Data were collected through an online questionnaire from 501 respondents representing 135 Industrial Forest Plantation (HTI) companies across Kalimantan. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0. The findings indicate that Work Environment, Organizational Culture, and Digital Literacy positively and significantly influence Job Satisfaction (R² = 0.727) and Employee Engagement (R² = 0.802). Job Satisfaction also exerts a strong effect on Employee Engagement (β = 0.734; p < 0.001). However, the moderating role of Generational Cohort was largely insignificant, except for a weak negative moderation on the Digital Literacy → Job Satisfaction path (β = –0.070; p = 0.013), indicating minimal generational differences. These results highlight that organizational factors outweigh generational differences in shaping employees’ work attitudes. Theoretically, this research extends the Job Demands–Resources (JD-R) model by incorporating digitalization dimensions, while practically, it offers insights for HR management to develop inclusive, technology-driven work environments that enhance satisfaction and engagement across generations.